Impact of sphingomyelin acyl chain (16:0 vs 24:1) on the interfacial properties of Langmuir monolayers: a PM-IRRAS study - Vázquez, Romina Laura (2019)
Membrane structure is a key factor for the cell`s physiology, pathology, and therapy. Evaluating the importance of lipid species such as N-nervonoyl sphingomyelin (24:1-SM) —able to prevent phase separation— to membrane structuring remains a formidable challenge. This is the first report in which polarization-modulated infrared reflection-absorption spectroscopy (PM-IRRAS) is applied to investigate the lipid-lipid interactions in 16:0 vs 24:1-SM monolayers and their mixtures with 1,2-Dioleoyl-sn-glycero-3-phosphocholine (DOPC) and cholesterol (Chol) (DOPC/SM/Chol 2:1:1). From the results we inferred that the cis double bond (Δ15) in 24:1-SM molecule diminishes intermolecular H-bonding and chain packing density compared to that of 16:0-SM. In ternary mixtures containing 16:0-SM, the relative intensity of the two components of the Amide I band reflected changes in the H-bonding network due to SM-Chol interactions. In contrast, the contribution of the main components of the Amide I band in DOPC/24:1-SM/Chol remained as in 24:1-SM monolayers, with a larger contribution of the non-H-bonded component. The most interesting feature in these ternary films is that the Cdouble bondO stretching mode of DOPC appeared with an intensity similar to that of SM Amide I band in DOPC/16:0-SM/Chol monolayers (a two-phase [Lo/Le] system), whereas an extremely low intensity of the Cdouble bondO band was detected in DOPC/24:1-SM/Chol monolayers (single Le phase). This is evidence that the unsaturation in 24:1-SM affected not only the conformational properties of acyl chains but also the orientation of the chemical groups at the air/water interface. The physical properties and overall H-bonding ability conferred by 24:1-SM may have implications in cell signaling and binding of biomolecules.